2007
DOI: 10.1007/s00246-007-0020-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Support with Milrinone Prior to Cardiac Transplantation in a Neonate with Left Ventricular Noncompaction Cardiomyopathy

Abstract: A 2-week-old female infant presented with acute decompensated left ventricular failure. Echocardiography diagnosed left ventricular noncompaction cardiomyopathy with dilated phenotype and a left ventricular shortening fraction <10%. The infant was mechanically ventilated for 2 weeks and then successfully extubated. She was maintained on intravenous milrinone for 6 months until she underwent successful orthotopic heart transplantation. Young children can be supported with inotropes for prolonged periods while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The left atrial ejection force as a marker of the left atrial systolic function may be increased in LVHT patients, suggesting compensating left atrial work against the dysfunctioning LV [86]. TDI velocities of the C-layer may be significantly reduced already in asymptomatic LVHT patients and thus may help to identify patients at risk for an adverse outcome [87][88][89]. STE may show twisting of the base and apex of the LV in the same direction when compared to controls and patients with dCMP where the LV rotation is clockwise on the basal level and counter-clockwise on the apical level [33].…”
Section: Echocardiographic Abnormalitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…The left atrial ejection force as a marker of the left atrial systolic function may be increased in LVHT patients, suggesting compensating left atrial work against the dysfunctioning LV [86]. TDI velocities of the C-layer may be significantly reduced already in asymptomatic LVHT patients and thus may help to identify patients at risk for an adverse outcome [87][88][89]. STE may show twisting of the base and apex of the LV in the same direction when compared to controls and patients with dCMP where the LV rotation is clockwise on the basal level and counter-clockwise on the apical level [33].…”
Section: Echocardiographic Abnormalitiesmentioning
confidence: 94%
“…Single patients have been reported to respond to milrinone [87]. In case of intractable heart failure and systolic dysfunction, despite optimal medical treatment, and mechanical desynchrony (widened QRS, reduced TDI velocities), CRT is indicated [88].…”
Section: Prevention Of Heart Failurementioning
confidence: 99%
“…The utility of chronic continuous milrinone infusion for heart failure as bridge therapy to heart transplantation was proposed in a recent adult study 6). McMahon et al29) demonstrated that long-term support with milrinone was safe and effective in infants with cardiomyopathy awaiting heart transplantation. Outpatient continuous parenteral inotropic therapy, including milrinone, has also been used in inotropic-dependent children with advanced heart failure 30).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all centers, nor geographical areas for that matter, have readily accessible transplant facilities. One study reported the successful long term support of a neonatal patient with INVM on milrinone while she awaited cardiopulmonary transplantation 22 …”
Section: Treatmentmentioning
confidence: 99%
“…One study reported the successful long term support of a neonatal patient with INVM on milrinone while she awaited cardiopulmonary transplantation. 22…”
Section: Treatmentmentioning
confidence: 99%